Exploring the impact of language on consumer-brand relationships across digital media - Greyling, Caroline (School of Management Studies, 2021)
Within the marketing management sphere, consumer-brand relationship theory has attracted interest and academic research since its inception. One area that has been relatively unexplored, however, is the interplay between vernacular languages and consumer-brand relationships in a multilingual South Africa. Celebrated for its multicultural and multilingual identity, South Africa recognises eleven official languages with English predominantly used across marketing activities. Despite a variety of research projects aimed at exploring consumer-brand relationship theory, there remains a gap in the knowledge regarding how languages impact the relationships that consumers form with brands. Previous research has been centred on the Western and Asian markets and has failed to address the challenges of the diverse South African market. Consumers experience an emotional link and a sense of attachment to their home language. This paper postulates that this connection extends to consumer-brand relationships and that language choice can, therefore, impact the formation and development of brand relationships. This paper sought to explore this theory, using qualitative research methods. In-depth interviews were conducted in order to collect information about consumers' experiences and feelings regarding this topic. Fourteen participants from various language groups were asked a series of open-ended questions and their responses recorded. Results demonstrated that the use of first languages can influence how consumers respond to brands and can affect a number of elements identified in the brand-relationship quality model. The analysis found a link between language use and brand relationship theory, finding that the use of consumers' mother tongues can lead to consumers developing relationship qualities including love and passion, self-connection and commitment. This demonstrates that language can play a significant role in impacting consumer-brand relationships. We, therefore, infer that language can potentially impact consumer-brand relationships, and that language choice has the power to impact how consumers build relationships with brands.